Thermo-elastic topology optimization and experimental characterization for multiphase structure with high thermal stiffness invariability - Yiming Fan; Guangkai Wei; Yuan Chen (Materials & Design)
Engineering structures are expected to steadily sustain a load with minimal deformation when subjected to thermal variation. In this study, we propose a multiphase structure with high thermal stiffness invariability (HTSI) and develop a method to topologically design such a structure using discrete material optimization (DMO). First, a series of quasi-static characterization tests under different temperatures was performed to assess the thermo-elastic properties of the multiphase material candidates. Second, an HTSI design method was proposed based on the multiphase material properties and DMO for acquiring both 2D and 3D multiphase structures. Last, a 3D multiphase structure was manufactured using additive manufacturing and corresponding experiments were performed to validate the effectiveness of the proposed method in the design of multiphase structures with HTSI. The results for 2D multiphase structures show that the HTSI design can ameliorate the fluctuation of structural compliance or stiffness when the temperature changes from 30 ℃ to 70 ℃. The fluctuations were reduced by 5.13 % and 20.3 % in the 2D cantilever and MBB beam, respectively, when compared to those produced via the general thermo-elastic (GTE) design. These results for designing 3D multiphase structures demonstrate that using the HTSI design can reduce thermally induced stiffness fluctuation by 24.4% when compared to the GTE design by experiments. The numerical accuracy was also validated with an error of only 7.7%.